Exploring The Phonological Words And Syllable Analysis - Fadlah Putri Sabila; Dwi Fatimah; Yani Lubis (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2023)
This article discusses phonology and syllables in the context of language. Phonology is a branch of linguistics that studies the sounds in language and the way they are organized, whereas syllables are the basic units in spoken language that form the basic structure of words. In this article, we explore the phonological words and syllable analysis, and the importance of understanding these concepts. In the phonological world, sounds in a language are categorized based on phonological characteristics such as voicing, place and manner of pronunciation, and others. This helps us understand how sounds are organized and combined in language to form meaningful meanings. In addition, the study of phonological worlds helps identify similarities and differences between languages ??and understand the basic structure of sounds in a given language. The syllable, as the core unit in spoken language, consists of the onset, nucleus, and coda. Syllable analysis helps us understand patterns and rules in the formation of words as well as the rhythm and phonotactics of language. In syllable analysis, we separate words into syllables and study the common syllable structures in that language. An understanding of syllables also has practical implications in language learning, speech therapy, and teaching language skills. Phonological and syllable analysis methods involve identifying the sounds of a language, analyzing syllable structures, and a comparative approach to comparison with other languages. Understanding these concepts is important in gaining a broader understanding of sound systems in language and how they affect human communication. Thus, this article illustrates the importance of phonological and syllable studies in understanding language structure, highlights the analytical methods used, and demonstrates implications and practical application of this knowledge in the context of language learning, speech therapy, and teaching language skills.